Study of Agricultural Scenario and Pattern of Labour Use in Different Crops (International Journal of Scientific Research in Science and Technology, 2025)
In this present paper, we studied the agricultural scenario and pattern of labour use in Bihar. The pattern of labour use by family, hired, male, and female components has been studied in the previous chapter by deriving varied relationships between farm size and different types of labour use. The relationship is established both- Horizontally (Regional Level) and Vertically (Farm Size Level). In fact, entire analysis is devoted to establish various relationship between farm size and pattern of labour use. One of the explanatory factor besides irrigation and cropping intensity is the cropping pattern which influences labour use. Therefore, it is essential to see the pattern of Labour use among different crops across various regions.